Principal Leadership in Implementing the Merdeka Curriculum: An Interdisciplinary Case Study in Indonesian Primary Education - Wira Zaky Fauzul Kabir (BRIDGE : The Multidisciplinary Research Portal, 2025)
This study examines the role of school principal leadership in implementing the Merdeka Curriculum at a public primary school in Indonesia using an interdisciplinary qualitative approach. Employing a qualitative descriptive design, data were collected through structured interviews, observations, and document analysis at SDN 1 Sidorejo, a school that has implemented the Merdeka Curriculum at the independent sharing stage. The findings indicate that effective curriculum implementation is strongly influenced by the principal’s ability to integrate managerial, supervisory, and instructional leadership roles. As a manager, the principal optimized limited resources and prioritized teacher development to support curriculum demands. Through academic supervision, the principal monitored instructional practices and provided feedback that contributed to gradual improvements in teaching quality. In addition, instructional leadership was reflected in efforts to foster teacher collaboration, encourage pedagogical innovation, and build a supportive learning culture. Despite positive outcomes, challenges were identified, including varying levels of teacher readiness, resistance to change, and limited access to technological resources. The study concludes that successful implementation of the Merdeka Curriculum requires sustained and adaptive school leadership capable of managing organizational change while supporting teachers’ professional growth. These findings contribute to the international literature on school leadership and curriculum reform, particularly in the context of primary education in resource-constrained settings.